Diastolic dysfunction on echocardiography does not predict survival after transjugular intrahepatic portosystemic stent‐shunt in patients with cirrhosis. Issue 6 (17th February 2019) - Armstrong, Matthew J.; Gohar, Farhan; Dhaliwal, Amritpal; Nightingale, Peter; Baker, Graham; Greaves, Daniel; Mangat, Kam; Zia, Zergum; Karkhanis, Salil; Olliff, Simon; Mehrzad, Homoyon; Steeds, Rick P.; et al.
Summary: Background: Cardiac dysfunction is frequently observed in patients with cirrhosis. There remains a paucity of data from routine clinical practice regarding the role of echocardiography in the pre‐assessment of transjugular intrahepatic portosystemic stent‐shunt. Aim: Our study aimed to investigate if echocardiography parameters predict outcomes after transjugular intrahepatic portosystemic stent‐shunt insertion in cirrhosis. Methods: Patients who underwent echocardiography and transjugular intrahepatic portosystemic stent‐shunt insertion at the liver unit (Birmingham, UK) between 1999 and 2016 were included. All echocardiography measures (including left ventricle ejection fraction; early maximal ventricular filling/late filling velocity ratio, diastolic dysfunction as per British Society of Echocardiography guidelines) were independently reviewed by a cardiologist. Predictors of 30‐day and overall transplant free‐survival were assessed. Results: One Hundred and Seventeen patients with cirrhosis (median age 56 years; 54% alcohol; Child‐Pugh B/C 71/14.5%; Model For End‐Stage Liver Disease 12) underwent transjugular intrahepatic portosystemic stent‐shunt for ascites (n = 78) and variceal haemorrhage (n = 39). Thirty‐day and overall transplant‐free survival was 90% (n = 105) and 31% (n = 36), respectively, over a median 663 (IQR 385‐2368) days follow‐up. Model for End‐Stage Liver Disease ( P  < 0.001) and Child‐Pugh Score ( P  = 0.002) significantly predicted 30‐day and overall transplant‐free survival. Model for End‐Stage Liver Disease ≥15 implied three‐fold risk of death. Six per cent (n = 7) of patients pre‐transjugular intrahepatic portosystemic stent‐shunt had a history of ischaemic heart disease and 34% (n = 40) had 1 or more cardiovascular disease risk factors. Fifty per cent (n = 59) had an abnormal echocardiogram and 33% (n = 39) had grade 1‐3 diastolic dysfunction. On univariate analysis none of the echocardiography measures pre‐intervention were related to 30‐day or overall transplant‐free survival post‐transjugular intrahepatic portosystemic stent‐shunt. Conclusions: Ventricular, in particular diastolic dysfunction in patients with cirrhosis does not predict survival after transjugular intrahepatic portosystemic stent‐shunt insertion. Model for End‐Stage Liver Disease and Child‐Pugh scores remain the best predictors of survival. Further prospective study is required to clarify the role of routine echocardiography prior to transjugular intrahepatic portosystemic stent‐shunt insertion. Abstract : LINKED CONTENT This article is linked to Jansen and Trebicka paper. To view this article visit, https://doi.org/10.1111/apt.15221 .